Women’s Role in Developing Economies: Case of Georgia - Kharistvalashvili, Nino (European Journal of Sustainable Development, 2016)
Abstract The paper deals with the most topical gender issues in economic point of view and explains women’s role in modern economy of developing country like Georgia.In spite of the powerful process of the globalization and dissemination of ideas of human rights and gender equality huge problems related with gender inequality still remains and hinders the social and economic development of the societies.The most prevalent issues regarding the abovementioned problem are the following: violence against women, pay gap between men and women workers, various stereotypes about the women existing in all over the world. All of these issues are dissected in an economic point of view.Georgia is a post-soviet country with its peculiarities that are also reflected with respect to the gender issues and the analysis given in the paper considers these important characteristics.In the modern world where women’s role in social and economic life is continuously increasing the issues of gender equality gains an utmost importance.Results of the study shows the ways for increasing women’s involvement in the economic processes in the country and using women’s skills and knowledge for the sake of the country. Key words: Gender, equality, economy, pay gap, migration, unemployment.